The chaperone HSPB1 prepares protein aggregates for resolubilization by HSP70 - Conrado C. Gonçalves (Nature Portfolio, 2021)
Abstract In human cells under stress conditions, misfolded polypeptides can form potentially cytotoxic insoluble aggregates. To eliminate aggregates, the HSP70 chaperone machinery extracts and resolubilizes polypeptides for triage to refolding or degradation. Yeast and bacterial chaperones of the small heat-shock protein (sHSP) family can bind substrates at early stages of misfolding, during the aggregation process. The co-aggregated sHSPs then facilitate downstream disaggregation by HSP70. Because it is unknown whether a human sHSP has this activity, we investigated the disaggregation role of human HSPB1. HSPB1 co-aggregated with unfolded protein substrates, firefly luciferase and mammalian lactate dehydrogenase. The co-aggregates formed with HSPB1 were smaller and more regularly shaped than those formed in its absence. Importantly, co-aggregation promoted the efficient disaggregation and refolding of the substrates, led by HSP70. HSPB1 itself was also extracted during disaggregation, and its homo-oligomerization ability was not required. Therefore, we propose that a human sHSP is an integral part of the chaperone network for protein disaggregation.